Why do we go to the zoo? : communication, animals, and the cultural-historical experience of zoos - Garrett, Erik A. (Fairleigh Dickinson University Press series in communication studies., 2014)
This book is a phenomenological investigation of the zoo visit experience. Why Do We Go to the Zoo is rooted in Husserlian phenomenology and focuses on the communicative interactions between humans and animals in the zoo setting. The book also provides the student examples of how to do phenomenology.